IMPLEMENTASI INTRUSION DETECTION SYSTEM (IDS)DI JARINGAN UNIVERSITAS BINA DARMA - Ulfa, Maria (Universitas Bina Darma, 2012)
Computer Security systems, in recent years has become a major focus in the world of computer networks, this is due to the high threat of suspicious (Suspicious Threat) and attacks from the internet. Bina Darma University is one of the agencies which activities using the internet network services, ranging from the processing of existing data, including the KRS online system, mail server and web portal in each unit and others. Bina Darma University network manager for this building system is a network Security by implementing a firewall and proxy server on each server in the network unit. To further optimize the network Security system at the University of Bina Darma, the author will implement a network Intrusion Detection System at the Bina Darma University as network Security solutions for both the intranet and internet network of Bina Darma University, where the author will build an IDS (Intrusion Detection System) using a snort. Keywords: Networking Security, Firewall, Proxy Server, IDS (Intrusion Detection System), Snort.